PESANTREN IN THE LINGUISTIC LANDSCAPE OUTLOOK: LANGUAGES AND THEIR USE IN ISLAMIC PUBLIC SPACES - Kamal Yusuf; Ica Oktaviana; Nisrina Aulia Nisa; Nurjannah Nurjannah (International Conference on Social and Islamic Studies, 2021)
This study reveals the use of language in the linguistic landscape phenomenon in the form oflanguage signs that exist in the pesantren environment. The purpose of this study was todetermine the use of language in public spaces in the pesantren environment. Furthermore,this research was conducted to find out what languages are used in language signs in thepesantren environment so that the function of language in the pesantren environment can beknown. The method used in this study is a qualitative descriptive method. Data collectiontechniques were carried out by direct observation and documentation. The results of thisstudy indicate that there are four languages used in language signs in the pesantrenenvironment. In addition, the use of language on language signs in the pesantren environmentfunctions as signboard markers, warning signs, and information signs.